Sudden Death in an Elderly Indonesian Hajj Pilgrim: A Case Report - Abidin, Zainal; Ikhsan, Mukhtar; Latif, Emi Misriah; Sinar, Anggasari; Forlentina, Silvia; Ekaningsih, Anyta (Health Access Journal, 2026)
There are 37% of Indonesian pilgrims in 2024 are elderly people aged ≥ 60 years. The elderly are a high-risk group for conditions such nocturnal disordered breathing, including Obstructive Sleep Apnea (OSA) especially severe physical fatigue in Hajj pilgrims. This descriptive case report concerns the death of an elderly hajj pilgrim in hotel. The data was collected from August to December 2025. It was obtained from the medical records of group’s Hajj medical team and interviews with the pilgrim’s roommate in Mekkah and her family in Indonesia. A 76-year-old female pilgrim with cardiovascular history was known without breathing while sleeping. She complained of fever, dizziness, and mild cough three days earlier. She received medical care from the medical team and her condition improved. That night, her roommate heard loud snoring followed by breathing sound gone while she slept. The medical team activated code blue and the Saudi Arabian emergency team declared that she died. In the medical check-up of Hajj pilgrims, screening of risk factor for suspected OSA needs to be done by health hajj management. The STOP-BANG questionnaire can be used to identify the high-risk of OSA in Hajj pilgrimage candidates. This can increase clinical awareness and mitigate the risk of death of Hajj pilgrims in hotels.